The Relationship Between Personal Hygiene Behavior With The Incidence Of Scabies In Pondok Pesantren Modern Darul Hikmah Kota Medan - Damanik, Muhammad Farid Zulkhair; Hemma Yulfi (Sumatera Medical Journal, 2020)
Introduction. Scabies is often found in Indonesia, which is due to its tropical climate. Data showed that the prevalence of scabies Indonesia in 2013 was 6%. Poor personal hygiene, low socioeconomic status, and non-supporting health behavior are also some of the risk factors. Objectives. To identify the relationship between personal hygiene behavior with scabies in Pondok Pesantren Modern Darul Hikmah Kota Medan. Methods. This is an analytical study using cross sectional design. The sample was all the students from grade 7-12. The data was taken cardinal signs of scabies and microscopic examination towards the scrapped skin. The risk factors on personal behavior was taken thru questionnaire and direct observation on the research site. Results. The incidence of scabies in Pondok Pesantren Modern Darul Hikmah Kota Medan is 81 out of 220 respondent (36,8%). There is a strong correlation between personal hygiene behavior with incidence of scabies in Pondok Pesantren Modern Darul Hikmah Kota Medan (p=0,001). The environmental sanitation is categorized poor according to 3 aspects including clean water availability, occupant density, and personal storage availability. Conclusion. There is a strong correlation between personal hygiene behavior with the incidence of scabies in Pondok Pesantren Modern Darul Hikmah Kota Medan.